Assessment of hematological toxicity and risk stratification in children aged 1-12 years with acute lymphoblastic leukemia receiving ALL COG protocol: a prospective observational study from a tertiary care center in central India - Yelam, Bapu; Rath, Sagarika; Ambedare, Tushar; Yelam, Jiji Bapu (International Journal of Contemporary Pediatrics, 2025)
Background: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy and while standardized chemotherapy protocols have improved survival, treatment-related haematological toxicities remain a significant challenge in low- and middle-income countries. Methods: A prospective observational study was conducted on 42 children aged 1–12 years with newly diagnosed ALL at a tertiary care center in Central India between 2023 and 2025. Clinical, hematological, immunophenotypic, cytogenetic and Minimal Residual Disease (MRD) data were collected and analyzed. Results: The cohort comprised 52.4% males, with mean age 7 years. B-cell ALL accounted for 83.3% of cases. Risk stratification revealed 64.3% intermediate-risk, 21.4% high-risk and 14.3% standard-risk. Pallor (85.7%) and fever (73.8%) were the most common presentations. Haematological toxicities particularly neutropenia, anemia and thrombocytopenia were more frequent in higher-risk groups and necessitated frequent transfusions. MRD negativity post-induction was achieved in 78.6% of patients and strongly correlated with remission (p<0.001). Conclusions: Haematological toxicities significantly impact survival in pediatric ALL, particularly in high-risk groups. MRD remains a powerful prognostic marker. Strengthening supportive care, infection prevention and strategies to reduce treatment abandonment are essential to improve outcomes in resource-limited settings.